Potential rebound effects of teleworking on residential and daily mobility. Issue 9 (25th August 2022) - Hostettler Macias, Laura; Ravalet, Emmanuel; Rérat, Patrick
Abstract: The practice of teleworking has been growing steadily in recent years with the development of ICT and the flexibilisation of work. The Covid‐19 pandemic and its stay‐at‐home restrictions have further accelerated this trend. As teleworking reduces the frequency of commuting, it also reduces CO2 emissions and may be seen as a tool to regulate mobility. However, and especially since working from home enables more flexible working, teleworking may have various 'rebound' effects on daily and residential mobility practices. Rebound effects include possible increases in the frequency or distance of journeys, such as an increase in non‐work‐related travel on teleworking days, as well as effects such as residential relocation or multilocal dwelling. In this article we intend to introduce and categorize the existing literature on the potential rebound effects of teleworking on residential and daily mobility. By critically assessing the literature we have identified the major lessons, while also noticing the limits of the research and a scarcity of qualitative approaches to understand how and why people who telework reinvest their non‐commuting time in other forms of mobility. Also missing in the literature is the longitudinal aspect, that is, the consideration of long‐term changes. These gaps have led us to formulate our proposition of a research agenda, where the lifestyle and life course approaches have emerged as crucial tools to understanding the motivations for teleworking and the respective rebound effects on residential and daily mobility.